An Exploratory analysis of the effects of climate change on vegetation: the case of Mutoko district in Mashonaland East Province, Zimbabwe - Mundowaya, Pfungwa Malvern (Midlands State University, 2014)
A plethora of researches have been done worldwide to determine and illustrate the effects of climate change on ecosystems, biodiversity especially on vegetation, using the most imperative climatic variables, rainfall and temperature which are of vital importance to plant species growth henceforth, determine biomes, ecosystem and woodlands plant species composition, structure and distribution. This study focused on effects of the climate change on vegetation in Mutoko District in Mashonaland East, Zimbabwe. The forestry inventory managed to assemble data for baseline reference to determine the demography of the district. The district is dominated by the miombo woodland interspersed with other woodlands species of combretum/terminalia, and acacia genera. During the last 3 decades rainfall and temperature have been changing in Mutoko District. In this research, trends in rainfall, maximum and minimum temperature at annual time-scale for the period 1978 – 2010 were analysed using a non-parametric test, Mann-Kendall and linear regression. The results indicated that rainfall and maximum temperature are positively increasing (S-statistic, r = 90; Tmax =39) but have statistically insignificant trends and minimum temperature is strongly negatively decreasing (S-statistic, Tmin = -160) hence a statistically significant trend. The information gathered from key informant interviews, revealed that majority of the respondents have a perception that the phenology of some indigenous fruit trees have shifted from their normal timing sequence. Thus, an overall analysis of the findings acquired in this study indicated that changes in climate have impacted on vegetation in Mutoko District as there are changes in yields, textural attributes (taste, colour, firmness shape, etc), fruit sizes and an upsurge of incidences of mortalities and disappearances of tree species. The researcher recommends that as changes in climate are in transition, it is difficult to ascertain future climate and vegetation scenarios, and further studies should be conducted based on individual species as they respond and adapt to climate change differently, in order to have the complete image of changes in vegetation, for sustainable utilization of forestry resources to improve rural livelihoods and food security, for instance there are cases of disappearance and mortality of plant species such as Sygyzium Guineense, Bauhinia Petersiana and Peltophorum Africanum. This might be the predicted transition phase and plant species are anticipated to be lost.